New Media for Educational Change Selected Papers from HKAECT 2018 International Conference (Educational Communications and Technology Yearbook,, 2018)
This book gathers selected papers presented at the Hong Kong Association for Educational Communications and Technology 2018 International Conference on the theme of "new media for educational change: effects on learning and reflection on practice". It contributes to a scholarly discussion that goes beyond what new media can contribute to education, and reflects on best practices as well as lessons learned by applying new media in a wide range of fields. Scholars from educational technology, journalism, higher education, etc. share their findings in a number of formats, such as empirical research, case studies of best practices, literature reviews, etc. The topics addressed include but are not limited to media practice, application of innovative technologies, MOOCs in higher education, social media for learning, gamification, learning analytics, and comparative studies.